The evaluation of rapid methods for monitoring free fatty acid levels in cheese - W.G. Ikins; H.S. Kwak; G.S. Zink; I.J. Jeon (Kansas Agricultural Experiment Station Research Reports, 1988)
The amount of free fatty acids present in cheese is important to dairy processors because these compounds make a significant contribution to the overall flavor. In this study, the results obtained using three relatively rapid methods of determining free fatty acids concentrations in cheese were compared to those acquired by using a more laborious but accurate gas chromatographic technique. One method, the Extraction-Titration Method, was found to be superior to the others because of its simplicity and reliability. In addition, the values obtained by this method were found to closely correlate with short chain fatty acid concentrations of cheese as determined by gas chromatography.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Free fatty acids; Cheese; Gas chromatography